Soldier and the state - "Huntington, Samuel P." (Dehradun, 2005)
This book present a theory of Civil-military relations. The reader will find much historical material, on the United states primarily, but also on Europe and Asia. Yet this book does not attempt an historical description of civil-military relations in general nor of any specific aspect of civil-military relations in particular.
Keywords: Civil-Military ralations-United states